Enhancement of colour quality, growth, and health status of rainbow Kurumoi fish Melanotaenia parva through dietary synthetic carotenoids supplementation - Meilisza, Nina; Suprayudi, Muhammad Agus; Jusadi, Dedi; Junior, Muhammad Zairin; Artika, I Made; Utomo, Nur Bambang Priyo (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT Carotenoids were known as pigment sources, the precursor of vitamin A, potential antioxidant and can improve the health status of fish. Furthermore, there are also studies that reveal the role of carotenoids in bone formation and metabolism. This study was conducted to determine the effect of different carotenoids at two different doses in the feed on growth, pigmentation, vitamin A conversion, blood profile, antioxidant activity, and calcium bone of the rainbow fish. Twenty-one aquariums with a volume of 20 L each stocked with 20 fish (1.08 ± 0.03 g of body weight and 4.56 ± 0.07 cm of body length). The experiment applied seven experimental diets (in triplicates) consisted of three types of carotenoids were astaxanthin (AS), canthaxanthin (CS), and lutein (LS) and two doses (130 and 260 mg/kg), i.e. AS-130, AS-260, CS-130, CS-260, LS-130, LS-260 and basal (without carotenoids) as the control. The fish were fed for 56 days of experimental period. The results showed that carotenoid diets were able to increase growth, total carotenoids, percentages of chromatophores, vitamin A conversion, erythrocyte, leukocytes, packed cell volume (PCV), neutrophils, and hemoglobin (Hb) compared to the control. Fish fed dietary astaxanthin at a level of 260 mg/kg was superior compared to other diets. Dietary carotenoids were also capable of decreasing the endogenous antioxidant activity of superoxide dismutase (SOD) and malonyl dialdehyde (MDA) and increased the calcium level in fish bone than basal diet. Keywords: carotenoids, growth, health status, Melanotaenia parva, pigmentation  ABSTRAK Karotenoid diketahui sebagai sumber pigmen, prekursor vitamin A, antioksidan potensial dan dapat meningkatkan status kesehatan ikan. Selain itu, karotenoid juga memiliki peran dalam formasi dan metabolism tulang. Penelitian ini dilakukan untuk mengevaluasi pengaruh jenis dan dosis karotenoid yang berbeda terhadap pertumbuhan, pigmentasi, konversi vitamin A, gambaran darah, aktifitas antioksidan dan kalsium tulang ikan rainbow Kurumoi. Sebanyak 20 ekor ikan (bobot tubuh rata-rata 1,08 ± 0,03 g dan panjang total rata-rata 4,56 ± 0,07 cm) dan diberi makan pakan yang mengandung karotenoid. Pakan uji terdiri atas tiga jenis karotenoid dengan tiga ulangan yaitu astaksantin (AS), cantaksantin (CS), dan lutein (LS) dan dua dosis (130 dan 260 mg/kg) dikodekan dengan AS-130, AS-260, CS-130, CS-260, LS-130, LS-260 dan basal (tanpa karotenoid) sebagai kontrol. Ikan diberi makan selama 56 hari pemeliharaan. Hasil penelitian menunjukkan bahwa karotenoid dapat meningkatkan pertumbuhan, total karotenoid, persentase kromatofora, konversi vitamin A, eritrosit, leukosit, hematokrit, neutrofil, dan hemoglobin dibandingkan dengan kontrol. Ikan yang diberi pakan mengandung astaksantin 200 mg/kg lebih baik dibandingkan denga pakan uji lainnya. Pakan yang mengandung karotenoid juga mampu menurunkan antioksidan endogenus superoxide dismutase (SOD) dan malonyl dialdehyde (MDA), serta meningkatkan kalsium tulang ikan dibandingkan pakan kontrol. Keywords: Melanotaenia parva, karotenoid, pertumbuhan, pigmentasi, status kesehatan.